The Lead–Lag Relationship Between Futures and Spot Price—A Case of the Oil and Oilseed Contracts Traded on Indian Exchange. Issue 1 (June 2021) - Joarder, Suranjana; Mukherjee, Diganta
In India, government intervention in the agricultural derivatives market has not allowed the market to grow and become an important tool of risk management. It has always been argued that the farmers and consumers of crops in India primarily operate in the spot market, and their expectations about the future market conditions are likely to be reflected in the spot price movements. If the farmers and consumers of the crops do not participate in the derivatives market, it is not expected to work as an efficient tool of information dissemination on the underlying commodity. We analysed the role played by the futures market in the price discovery process in this article. To test whether the futures or spot market in India plays a dominant role in information dissemination, we have done a regression analysis considering the lagged futures and spot price volatility as explanatory variables. We consider the major oil and oilseed contracts traded on National Commodity and Derivatives Exchange. As the uses of many of the oilseeds are related, we have tried to analyse the interlinkages among the market for different commodities. Our results clearly show that information on relevant futures market volatilities help significantly to assess the volatility in the spot markets. This linkage can be leveraged to manage the spot market risks better. JEL: G10, G13, G14